Modeling the effect of economic efforts to control population pressure and conserve forestry resources - Lata, Kusum; Misra, Arvind Kumar Kumar (Nonlinear Analysis: Modelling and Control, 2017)
The increase in human population poses a great menace for the forestry resources. Therefore, protection and conservation of forestry resources is a challenging subject across the globe. Keeping this point in view, we propose and analyze a nonlinear mathematical model to assess the effect of economic efforts applied to control population pressure as well as to increase forestry resources by plantation on the conservation of forestry resources. The condition when one should spend more money on plantation/reducing population pressure has been obtained. Numerical simulation is also performed to support analytical findings and identify the important parameters useful for the conservation of forestry resources.